2013
DOI: 10.1038/aja.2013.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luteinizing hormone and androgen on the development of rat progenitor Leydig cells in vitro and in vivo

Abstract: Progenitor Leydig cells are derived from stem cells. The proliferation and differentiation of progenitor Leydig cells significantly contributes to Leydig cell number during puberty. However, the regulation of these processes remains unclear. The objective of the present study was to determine whether luteinizing hormone (LH) or androgen contributes to the proliferation and differentiation of progenitor Leydig cells. Fourteen-day-old male Sprague-Dawley rats were treated for 7 days with NalGlu, which is a gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…LH is essential for Leydig cell function because it is the principle stimulating hormone of androgen production in adult Leydig cells (1). Previous studies have shown that LH stimulated the development of rat progenitor Leydig cells into immature Leydig cells (5,11,20). In this study, we used 1 ng/ml LH instead of 100 ng/ ml because high concentration of LH can cause LHCGR internalization (28,29), and we also used a 2-day culture in which immature Leydig cells still maintained strong androgen production.…”
Section: Discussionmentioning
confidence: 99%
“…LH is essential for Leydig cell function because it is the principle stimulating hormone of androgen production in adult Leydig cells (1). Previous studies have shown that LH stimulated the development of rat progenitor Leydig cells into immature Leydig cells (5,11,20). In this study, we used 1 ng/ml LH instead of 100 ng/ ml because high concentration of LH can cause LHCGR internalization (28,29), and we also used a 2-day culture in which immature Leydig cells still maintained strong androgen production.…”
Section: Discussionmentioning
confidence: 99%
“…The testicular localization of GnIH and its receptor GPR147, in both mammals and birds, opens new perspectives in the autocrine/paracrine control of testicular activity suggesting a possible interplay between GnRH and GnIH in order to modulate T secretion and spermatogenesis ( 29 ). Furthermore, GnRH activity in Leydig cells is not restricted to T production but is extended to the development of rat progenitor Leydig cells both in vivo and in vitro ( 30 ).…”
Section: Gnrh a Historical Modulator Of Testis Physiologymentioning
confidence: 99%
“…Consequently, adult Leydig cells must develop from stem/progenitor cells (22,23). Numerous studies in rodents have investigated how adult Leydig cells differentiate from progenitor cells at puberty and have identified a number of factors involved (19,22,(24)(25)(26)(27)(28)(29). However, such studies focus around the period when stem/progenitor cells have started along the differentiation pathway into adult Leydig cells.…”
mentioning
confidence: 99%